A Systematic Literature Review On Lightweight Secured S-box Design For Mhealth Applications - Nur Hafiza Zakaria; Tasnuva Ali; Azni Hazlizan Ab Halim (UNISEL, 2024)
The process of designing powerful and secured S-Boxes is becoming an essential constituent in the field of modern cryptography. Different S-Box designs have been proposed to make it more suitable for IoT, mHealth and WBAN applications but proper implementation is still deficient for their design complexity. In this paper, major criteria of S-Boxes for mHealth systems were conducted following a systematic literature review process and required findings were outlined. The paper also demonstrates the current designs in different areas like security, low power and less memory to find out the challenges and opportunities for designing a new S-Box in modern mHealth applications. Finally, the SLR also gives a research direction to choose major design properties of new S-Boxes for mHealth as well as IoT applications. After evaluating the result, this paper also suggested a composite S-Box with the 3D design based on rotation, shifting and Galois Field 24 to (22)2 pipelining structures for less memory, power and secured applications. Thus, the intimation of Systematic Literature Review (SLR) is to give a clear concept to future researchers in the area of composite 3D S- Box design in terms of security in mHealth applications.